2010
DOI: 10.1128/jb.00659-10
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Acetyl Esterase Domain Targets Diverse Bacteriophages to the Vi Capsular Receptor of Salmonella enterica Serovar Typhi

Abstract: A number of bacteriophages have been identified that target the Vi capsular antigen of Salmonella enterica serovar Typhi. Here we show that these Vi phages represent a remarkably diverse set of phages belonging to three phage families, including Podoviridae and Myoviridae. Genome analysis facilitated the further classification of these phages and highlighted aspects of their independent evolution. Significantly, a conserved protein domain carrying an acetyl esterase was found to be associated with at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
93
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 37 publications
1
93
0
1
Order By: Relevance
“…Their location is not random, and many phage-encoding virulence factors have been found near the tail fiber regions (80). By further analysis with HHpred, we found that the prophage-related genes in HPR IV of JM-2012, which are adjacent to the tail fiber-related genes, were similar to those of the S. enterica serovar Typhi phage Vi type I tail spike-carrying acetylxylan esterase domain (81), and this portion of HPR IV, which includes the HJR, phage muramidase, prophage-related, and tail fiber-related genes, may be similar to the pathogenicity islet in S. enterica serovar Typhi that is critical for toxin secretion (67). Although it is unclear whether their positional relationships within HPRs are strategic, this finding prompted us to speculate on some potential mechanisms underlying the movement of transferable elements.…”
Section: Discussionmentioning
confidence: 83%
“…Their location is not random, and many phage-encoding virulence factors have been found near the tail fiber regions (80). By further analysis with HHpred, we found that the prophage-related genes in HPR IV of JM-2012, which are adjacent to the tail fiber-related genes, were similar to those of the S. enterica serovar Typhi phage Vi type I tail spike-carrying acetylxylan esterase domain (81), and this portion of HPR IV, which includes the HJR, phage muramidase, prophage-related, and tail fiber-related genes, may be similar to the pathogenicity islet in S. enterica serovar Typhi that is critical for toxin secretion (67). Although it is unclear whether their positional relationships within HPRs are strategic, this finding prompted us to speculate on some potential mechanisms underlying the movement of transferable elements.…”
Section: Discussionmentioning
confidence: 83%
“…The complete genome of phage SPN3US revealed a length of 240,413 bp with a GϩC content of 48.54%, 264 ORFs, and two tRNAs, suggesting the largest Salmonella phage genome found to date (10). The average gene length is 855 bp, and the gene density is 1.098/kb.…”
mentioning
confidence: 97%
“…From the O157 phages, AKFV33, Rv5, wV8, AR1, SFP10 and CBA120 are completely sequenced (GenBank accession numbers NC_017969.1, NC_011041.1, NC_ 012749.1, AP011113.1, HQ259103.1 and JN593240.1, respectively). Analysis of the PhaxI genome via BLASTN shows a high similarity to Viunalike phages, namely Salmonella phages ViI (Pickard et al, 2010), SFP10 (Park et al, 2012) and PhiSH19 (Hooton et al, 2011), Escherichia phage vB_EcoM_CBA120 , Shigella phage phiSboM-AG3 (Anany et al, 2011), and Dickeya phage vB_DsoM_LIMEstone1 (Adriaenssens et al, 2012b) (GenBank accession numbers FQ312032.1, HQ259103.1, JN126049.1, JN593240.1, FJ373894.1 and HE600015.1, respectively).…”
Section: Discussionmentioning
confidence: 99%